Adherence to antiretroviral therapy and HIV transmission risks: implications for test-and-treat approaches to HIV prevention. - Kalichman, Seth C; Cherry, Chauncey; Amaral, Christina M; Swetzes, Connie; Eaton, Lisa; Macy, Rene; Grebler, Tamar; Kalichman, Moira O (AIDS patient care and STDs, 2010)
HIV transmission may be prevented by effectively suppressing viral replication with antiretroviral therapy (ART). However, adherence is essential to the success of ART, including for reducing HIV transmission risk behaviors. This study examined the association of nonadherence versus adherence with HIV transmission risks. Men (n = 226) living with HIV/AIDS and receiving ART completed confidential computerized interviews and telephone-based unannounced pill counts for ART adherence monitoring. Data were collected between January 2008 and June 2009. Results showed that nonadherence to ART was associated with greater number of sex partners and engaging in unprotected and protected anal intercourse. These associations were not moderated by substance use. The belief that having an undetectable viral load leads to lower infectiousness was associated with greater number of partners, including nonpositive partners, and less condom use. Men who had an undetectable viral load and believed that having an undetectable viral load reduces their infectiousness, were significantly more likely to have contracted a recent STI. Programs aimed at testing and treating people living with HIV/AIDS for prevention require attention to adherence and sexual behaviors.
Keywords: Adult; Anti-HIV Agents; Condoms; Health Knowledge, Attitudes, Practice; HIV Infections; HIV-1; Homosexuality, Male; Humans; Interviews as Topic; Male; Medication Adherence; Middle Aged; Risk-Taking; Sexual Behavior; Sexual Partners; Viral Load